Zirconia crowns as an esthetic alternative for oral rehabilitation in pediatric dentistry: A review. Issue 3 (December 2021) - Rocha, Marina Carvalho Mendes; Inácio, Gisele Carvalho; Taira, Thaise Mayumi; Delgado, Renata Zoraida Rizental; Maciel, Sandra Mara; Frítola, Márjori
Abstract: Background: The success of rehabilitation in primary teeth may not rely only on the success of dental restoration, as esthetics is also important. As zirconia crowns combine resistance with esthetics, pediatric dentists must know the details regarding this material to be able to use it when required. Objective: To review the literature and synthesize research regarding the use of prefabricated zirconia crowns. Material and methods: A systematic search of the literature was carried out in PubMed, MEDLINE EBSCO, BVS, Embase, and Scopus, with the search terms: "zirconia crowns", "zirconia crown", "prefabricated crowns", "pediatric crowns", "zirconia pediatric crown", "deciduous", " primary teeth", "primary tooth", "pediatric dentistry", "primary molar" and "primary incisors". After the screening for inclusion and exclusion criteria, 60 eligible articles were included, in English, Spanish or Portuguese, with no restrictions on the year of publication. Results: Zirconia crowns are indicated for primary teeth affected by early childhood caries, traumatic dental injuries and developmental defects of enamel. They present resistance, durability, higher esthetics proprieties (when compared to other materials for the full coronal coverage of primary teeth), good gingival health and biocompatibility, good parental and children's acceptance and satisfaction. However, some limitations are mentioned: higher costs, the necessity for greater amounts of tooth reduction and the impossibility of adjustments. Conclusion: Zirconia crowns, as no other material for the full coronal coverage of primary teeth, combine biocompatibility, resistance and ideal esthetic outcomes. This material, despite its limitations, is a great alternative for the rehabilitation of primary teeth with intense loss of structure.